ICT Integration in Mathematics Teaching and Learning Activities: A Literature Review - Sharma Chapai, Krishna Prasad (International Research Journal of MMC, 2023)
This review aims to assess the current state of knowledge on the role of ICT in teaching and learning mathematics, with the goal of identifying effective approaches and strategies that can be employed to enhance mathematics education through the use of ICT. It also focuses on the possible advantages of ICT integration in mathematics instruction. The study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to review the related literature. The related literature was searched using key terms such as "ICT," "mathematics education," and "teaching-learning activities" in electronic databases such as ERIC, Google, Google Scholar, Scopus, and Web of Science. The search was limited to 22 articles published from 2015 to 2023. The findings of this study show that the attitude of teachers and students toward using ICT in teaching and learning mathematics was found to be positive; however, they faced the problem of integrating ICT in mathematics in the fields of algebra, statistics, vectors, geometry, and analysis. To effectively integrate ICTs into mathematics instruction, educational institutions must offer the necessary training to teachers.